2019
DOI: 10.1111/vde.12715
|View full text |Cite
|
Sign up to set email alerts
|

Proactive maintenance therapy of canine atopic dermatitis with the anti‐IL‐31 lokivetmab. Can a monoclonal antibody blocking a single cytokine prevent allergy flares?

Abstract: Background -Once the signs of canine atopic dermatitis (AD) are controlled, the proactive application of topical glucocorticoids can delay disease flares.Objectives -We wished to determine if the proactive administration of the anti-IL-31 lokivetmab would prevent or delay flares of canine AD.Animals -We tested this strategy in four Maltese-beagle atopic dogs before enrolling 21 dogs with spontaneous AD.Methods and materials -In our acute AD model, house dust mite (HDM)-sensitized dogs were injected once with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
5
30
0
1
Order By: Relevance
“…When comparing the clinical benefit of blocking IL-31 in horses with other species, we noticed a reduction of skin lesion severity in IBH-affected horses, which is in contrast to atopic dermatitis trials in dogs and humans that only showed reduction of pruritus whereas no improvement of eczema. 37,42 This suggests a meaningful impact of the self-inflicted trauma in horses with IBH. Although an anti-IL-31 therapy will not prevent the allergic reaction itself, it might represent an option stopping the vicious circle of self-reinforcing pruritus to alleviate clinical symptoms.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…When comparing the clinical benefit of blocking IL-31 in horses with other species, we noticed a reduction of skin lesion severity in IBH-affected horses, which is in contrast to atopic dermatitis trials in dogs and humans that only showed reduction of pruritus whereas no improvement of eczema. 37,42 This suggests a meaningful impact of the self-inflicted trauma in horses with IBH. Although an anti-IL-31 therapy will not prevent the allergic reaction itself, it might represent an option stopping the vicious circle of self-reinforcing pruritus to alleviate clinical symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Comparably to the mAb against IL‐31, we suggest that the vaccine‐induced anti‐IL‐31 antibodies mitigate the IL‐31‐mediated pruritus and thus lowering the self‐inflicted trauma caused by the horse scratching its skin. When comparing the clinical benefit of blocking IL‐31 in horses with other species, we noticed a reduction of skin lesion severity in IBH‐affected horses, which is in contrast to atopic dermatitis trials in dogs and humans that only showed reduction of pruritus whereas no improvement of eczema . This suggests a meaningful impact of the self‐inflicted trauma in horses with IBH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in canine atopic dermatitis, anti-canine IL-31 antibody (lokivetmab) significantly inhibited scratching in dogs with canine atopic dermatitis [82][83][84][85]. Proactive treatment with lokivetmab also reduced the flare of canine atopic dermatitis [85].…”
Section: In Clinical Trialmentioning
confidence: 99%
“…Such approaches using nemolizumab (CIM331) have recently been tested successfully (also in terms of reducing itch) in atopic dermatitis in both humans and other primates (19, 20, 4446). Similarly, the anti-canine-IL-31 monoclonal antibody, lokivetmab, has been used to treat atopic dermatitis in dogs (4749). However, the potential clinical benefits of anti-IL-31 monoclonal antibodies have yet to be reported for CsU (and indeed other autoimmune skin diseases).…”
Section: Il-31 In Autoimmune Skin Diseasesmentioning
confidence: 99%